Technology of Using art-Pedagogy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article reveals the content and essence of art- pedagogy. Particular attention is paid to teaching methods using art- pedagogy. Learning using art pedagogy is based on serving the professional development of students.